Evaluation of physical phenomena and surface integrity during hydroabrasive disintegration of the rotating workpiece with feedback loop control. (February 2019) - Cárach, Ján; Hloch, Sergej; Petrů, Jana; Müller, Miroslav; Hromasová, Monika; Nag, Akash; Čuha, Dominik; Hlaváček, Petr; Hatala, Michal; Kratochvíl, Jiří; Ruggiero, Alessandro
Highlights: New device for hydroabrasive disintegration of rotating workpieces was tested. This study uses acoustic emission for on-line control in the form of an adaptive connection. Increasing in traverse speed, the signal intensities decrease due to shorter interaction time. Focuses on the acquisition of theoretical knowledge about the technology with the aid of SEM surface analysis. Abstract: The paper deals with the potential of employing accompanying physical phenomena, acoustic emissions, during monitoring of abrasive water jet disintegration of rotating workpiece. It focuses on the acquisition of theoretical knowledge about this technology with the aid of SEM surface analysis. Variation in traverse speed of the cutting head is used during the experiments. All values were obtained during experimental materials turning by AWJ method. The surfaces were scanned using optical profilometer MicroProf FRT to obtain surface roughness parameters such as Ra (10.75 µm–22.5 µm), Rq (13.75 µm–28.25 µm) and Rz (88 µm–166 µm). The result includes the possibility of on-line control in the form of an adaptive connection, which applies information gathered by an array of sensors and its transformation into a digital form. The acquired signals represent that with increase in traverse speed, the signal intensities decrease due to shorter interaction time. SEM images provide characteristics of surfaces created by HADRO process such as craters, peaks and valleys, micro-cracks and striations marks.